Managing professional knowledge boundaries during ECHO telementoring consultations in two Veterans Affairs specialty care liver clinics: A theme-oriented discourse analysis. (April 2019) - Koenig, Christopher J; Wenger, Matthew; Graham, Glenn D; Asch, Steven; Rongey, Catherine
Introduction: Consultations are the traditional method of communication between generalist and specialist providers managing patients with specialty care needs. Traditional written consultations have limitations, including inadequate clinical information and inappropriate, or unclear consultation questions. Teleconsultations minimize these limitations through real-time communication between generalist and specialist providers to actively manage professional knowledge boundaries about specialty care problems. Methods: We video-recorded 37 teleconsultation sessions, resulting in 115 consultations between generalist and specialty care providers participating in Veterans Affairs (VA) Extension for Community Healthcare Outcomes (ECHO) liver clinics. Data were collected at two US sites across nine months to observe consultation communication among 33 primary care generalists and three liver specialists. Video recordings were transcribed verbatim and analysed using theme-oriented discourse analysis to characterize consultation question content and format. Results: Generalists' consultation question content addressed a range of topics, including treatment, diagnosis, interpreting results, patient communication, screening and surveillance, and care coordination. Some generalists relied on descriptive narratives rather than a specific question to convey complex patient cases. Consultation question format showed nearly even division between targeting general medical knowledge and specialty care knowledge domains, including specialty care, medical, organizational, and experiential knowledge. Discussion: Timely access to specialists through teleconsultation has the potential to transform specialty care delivery. This article examines provider-to-provider interactions to understand how the communication process contributes to knowledge management during teleconsultations. Video studies of health information technology use provide a rich opportunity for analysing real-time communication that may help improve cross-specialty collaboration and the coordinated management of patients with specialty care needs.